Analysis the Implementation Ministry of Transportation Decree Number KM 65 of 2009 in Shipping Crimes - Ardiansyah, Yusuf Amir; Umlati, Dandi; Yasdin, Ewi; Faisal, Muhammad; Hasibuan, Amirul Adli Habib (JUSTISI, 2025)
The study aims to analyze the effectiveness of the implementation of the Decree of the Minister of Transportation Number KM 65 of 2009 concerning the Standard of Non-Convention Vessels (Non Convention Vessel Standard) Flagged by Indonesia in a criminal act of shipping in Sorong Waters. The author uses a normative legal approach with a descriptive analysis method. The descriptive analysis method is an analysis method that focuses on case problems, then linked to existing legal principles and conclusions are drawn from the analysis. The data collection technique uses a secondary data collection method consisting of primary legal materials in the form of legal regulations or the results of judges' decisions that have been final and binding, and secondary legal materials in the form of scientific research journals compiled by legal experts. In this study, the author found that there had been a waiver of the KM 65 of 2009 regulation by the judge in a case of a criminal act of shipping violation with Decision number: 267 / Pid.B / 2023 / PN Son. In this mn case, the judge made a mistake by not conducting a thorough examination. The judge's mastery of shipping regulations is considered very weak. The judge has the authority to ask the public prosecutor to present an expert, namely the Harbor Master, to request expert information and also clarification on the Sailing Approval Letter that has been issued by him. There are quite a lot of shipping regulations so that the presence of an expert is needed to provide input to the judge on the technical regulations of the ship. Law enforcers in Indonesia are accustomed to focusing their views on a regulation at the level of the Law which already contains sanctions and types of violations. Therefore, the author is of the opinion that the regulation KM 65 of 2009 concerning the Indonesian-flagged Non-Convention Vessel Standard must be formed at the level of the Law and the presence of an expert in the legal field is needed to explain clear legal regulations so as to minimize the judge's error in a regulation. These two things must be done so that the case of ignoring the regulation KM 65 of 2009 does not happen again, and the economic activities of shipping are not disrupted due to incorrect law enforcement.